PEMANFAATAN TEKNOLOGI FEROSEMEN OLEH RELAWAN MDMC UNTUK MEREHABILITASI DAN MEREKONSTRUKSI RUMAH RUSAK AKIBAT BENCANA GEMPA BUMI - Gunasti, Amri; Laili, Januariya (Jurnal Abdi Insani, 2024)
The community already understands the ability of the Muhammadiyah Disaster Management Center (MDMC) to carry out mitigation, preparedness, emergency response and handling of victims. It's just that so far MDMC has not been able to carry out reconstruction and rehabilitation of houses that have cracked due to earthquakes. In the future, this shortcoming can be minimized by providing assistance in applying ferrocement technology to rehabilitate and reconstruct houses cracked due to shocks caused by earthquakes. There are two problems faced by this institution, first, volunteers still do not understand the technical causes and technology that can be used to overcome cracks in the walls of houses due to earthquakes. Second, volunteers do not have the skills to reconstruct and rehabilitate the walls of houses that have cracked due to earthquakes. The objectives of this activity are first, MDMC volunteers understand how biopore technology works, second, MDMC Volunteers are Skilled in Applying Ferrocement Technology for Rehabilitation and Reconstruction of Houses Due to Earthquake Disasters. There are two things that must be done to achieve these two targets. The two things are, first, providing guidance and counseling on ferrocement technology, second, providing simulations of the application of ferrocement technology. After being given assistance, counseling and simulation, the ability of volunteers increased by 48.75. Before the activity was held, the ability of volunteers was in the less category. After the activities of the service program in the Muhammadiyah association, volunteer activities increased to the excellent category.